The Seamless World: A Spatial Model of International Specialization. - Krugman, P; Venables, A (National Bureau of Economic Research, 1995)
This paper is an effort to do international trade theory without mentioning countries. Nearly all models of the international economy assume that trade takes place between nations or regions which are themselves dimensionless points. We develop a model in which economic space is instead assumed to be continuous, and in which this 'seamless world' spontaneously organizes itself into industrial and agricultural zones because of the tension between forces of agglomeration and disagglomeration. One might expect such a model to be analytically intractable, but we are able to gain considerable insight through a combination of simulations and an analytical approach originally suggested in a biological context by Alan Turing.